2019
DOI: 10.1007/s10508-019-1404-y
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual Identity and Behavior Among U.S. High School Students, 2005–2015

Abstract: Sexual orientation is a multidimensional construct which is increasingly recognized as an important demographic characteristic in population health research. For this study, weighted Youth Risk Behavior Survey (YRBS) data were pooled across 47 jurisdictions biennially from 2005 to 2015, resulting in a national sample of 98 jurisdiction-years (344,815 students). Respondents were a median of 15.5 years, 49.9% male, and 48.8% White. Sexual identity and behavior trends from 2005 to 2015 were assessed with logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 52 publications
(75 reference statements)
2
27
0
Order By: Relevance
“…Increases in reported sexual minority orientation and same-sex sexual contacts could reflect either increased comfort with reporting or underlying population changes in sexual orientation. The observed increases in the proportion of the population reporting being sexual minorities are consistent with evidence from US adolescents 19 and from British adults. 18 Although suicide attempts declined over time among students identifying as sexual minorities, suicide attempts remained elevated among sexual minorities compared with heterosexual students.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Increases in reported sexual minority orientation and same-sex sexual contacts could reflect either increased comfort with reporting or underlying population changes in sexual orientation. The observed increases in the proportion of the population reporting being sexual minorities are consistent with evidence from US adolescents 19 and from British adults. 18 Although suicide attempts declined over time among students identifying as sexual minorities, suicide attempts remained elevated among sexual minorities compared with heterosexual students.…”
Section: Discussionsupporting
confidence: 82%
“…30,31 A strength of the study is that we used data representative of adolescents in each state. Whereas authors of a previous study on sexual orientation over time also used YRBSS data, 19 our approach of only including states that collected sexual orientation data continuously throughout the study period allowed us to evaluate changes in sexual orientation in the same population over time. At the same time, the number of included states was small and represented only the northeast, mid-Atlantic, and Midwest, meaning the results may only be generalizable to these regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding dispositional variables, sexual orientation is a relevant multidimensional construct that has been widely evaluated in the adult population [ 45 , 46 ]. However, the prevalence of sexual minority identity has rarely been examined in adolescents [ 47 ]. In the present study, 6% of the sample identified as lesbian, gay, or bisexual (LGB) and 3.6% did not define their sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, non-heterosexuality has not increased to the same extent amongst men as it has amongst women (England, Mishel, & Caudillo, 2016;Phillips et al, 2019). The sexual identity label trajectories of men are also likely to differ from those of women sample of women to the experiences of men.…”
Section: Study Limitationsmentioning
confidence: 99%